Between Martyrdom and Mobilization: Women’s Participation in Karnataka’s Nationalist Movement - Somanakatti Bhimavati (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This paper examines the significant yet often underrepresented role of women in Karnataka’s nationalist movement between the late 19th and mid-20th centuries. It highlights how women participated not only as supporters but as active revolutionaries, mobilizers, and martyrs. Drawing on secondary data, government archives, and published reports, the study explores the contributions of prominent figures such as Kittur Rani Chennamma, Onake Obavva (symbolic inspiration), Kamaladevi Chattopadhyay, and grassroots women activists during Quit India and Civil Disobedience Movements. Women’s engagement took diverse forms-ranging from organizing protests, distributing underground literature, to leading satyagraha’s. Despite patriarchal constraints, their mobilization efforts contributed to shaping Karnataka’s socio-political consciousness. The study employs a historical-analytical method and qualitative content analysis of archival records and scholarly works. It identifies key mobilization networks, local organizations, and the impact of women’s activism on national politics. The paper also addresses the historiographical gap in documenting regional women’s contributions and argues for integrating their narratives into mainstream nationalist history.